Managing multiple pressures for cetaceans' conservation with an Ecosystem-Based Marine Spatial Planning approach. (1st June 2021) - Carlucci, Roberto; Manea, Elisabetta; Ricci, Pasquale; Cipriano, Giulia; Fanizza, Carmelo; Maglietta, Rosalia; Gissi, Elena
Abstract: Despite the recognized important ecological role that cetaceans play in the marine environment, their protection is still scarcely enforced in the Mediterranean Sea even though this area is strongly threatened by local human pressures and climate change. The piecemeal of knowledge related to cetaceans' ecology and distribution in the basin undermines the capacity of addressing cetaceans' protection and identifying effective conservation strategies. In this study, an Ecosystem-Based Marine Spatial Planning (EB-MSP) approach is applied to assess human pressures on cetaceans and guide the designation of a conservation area in the Gulf of Taranto, Northern Ionian Sea (Central-eastern Mediterranean Sea). The Gulf of Taranto hosts different cetacean species that accomplish important phases of their life in the area. Despite this fact, the gulf does not fall within any area-based management tools (ABMTs) for cetacean conservation. We pin down the Gulf of Taranto being eligible for the designation of diverse ABMTs for conservation, both legally and non-legally binding. Through a risk-based approach, this study explores the cause-effect relationships that link any human activities and pressures exerted in the study area to potential effects on cetaceans, by identifying major drivers of potential impacts. These were found to be underwater noise, marine litter, ship collision, and competition and disturbance on preys. We draw some recommendations based on different sources of available knowledge produced so far in the area (i.e., empirical evidence, scientific and grey literature, and expert judgement) to boost cetaceans' conservation. Finally, we stress the need of sectoral coordination for the management of human activities by applying an EB-MSP approach and valuing the establishment of an ABMT in the Gulf of Taranto. Highlights: Cetaceans' conservation addressed through a risk-based approach. Evidence collected from multiple knowledge sources and uncertainty analysed. Multiple drivers of pressures from maritime and land-based activities identified. Cause-effects analysis of direct and indirect pressures on cetaceans developed. Ecosystem-based MSP suitable to control pressures from activities outside MPAs.